Analisa Program Bantuan Beras Sejahtera (Rastra) dalam Meningkatkan Kesejahteraan Masyarakat di Desa Serdang Indah Kecamatan Luas Kabupaten Kaur Provinsi Bengkulu - Dodi, Yusman; Ekaputri, Retno Agustina; Izharudin, Izharudin (Ecoplan, 2024)
This study aims to analyze the effectiveness of the Rastra program in Batu Lungun Village, Nasal District. This study uses a descriptive qualitative approach. Data was collected by distributing questionnaires to 3 respondents from village officials, three from the Village Consultative Council, eight from Rastra entrepreneurs, and 30 from PPM Rastra. Data were collected through questionnaires distributed technique to 3 respondents from village officials, three respondents from the Village Consultative Body, eight from business Rastra, and 30 others from the Domestic Beneficiaries Rastra. Data was also collected through interview techniques from 1 respondent from village officials, one respondent from the Village Consultative Body, two respondents from Tim business Rastra, and three respondents from poor households. Data were analyzed using percentage analysis using a Likert scale and analysis of the interview results. The results showed that the effectiveness of the rice program for poor families (Rastra) has not been optimally achieved. Of 6 indicators of program success, Rastra, 3 of which have yet to reach both criteria. The indicator was on target, the right price and the right quality. Rastra channeled still not right given to Households that did meet the criteria for poor households, rice they received was also in poor condition, and redeemed at a price higher than the price determination Rastra general guidelines.